Anti-Swing Fuzzy Controller Applied in a 3D Crane System - Antic, D.; Jovanovic, Z.; Peric, S.; Nikolic, S.; Milojkovic, M.; Milosevic, M. (Engineering, Technology & Applied Science Research, 2012)
It is well known that fuzzy logic can be used in the control of complex systems described by highly nonlinear mathematical models. However, the main difficulty in the design of a fuzzy controller comes with the adjustment of the controller’s parameters that are usually determined by human experts’ knowledge or trial and error methods. In this paper, we describe an implementation of fuzzy logic in order to reduce oscillations during the positioning of a 3D crane system. The fuzzy controller’s structure is quite simple, requiring only two input variables. The proposed fuzzy controller has been applied to an experimental laboratory framework and results show that oscillations are significantly reduced.